2018
DOI: 10.1080/02770903.2018.1452934
|View full text |Cite
|
Sign up to set email alerts
|

Effect of omega-3 fatty acids supplementation during pregnancy on lung function in preschoolers: a clinical trial

Abstract: Prenatal DHA supplementation did not influence pulmonary function in this cohort of Mexican preschoolers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Pathophysiological changes were mainly due to increased Qs/Qt and imbalance of ventilation/blood flow ratio [ 37 ]. The application of omega-3 fatty acids not only can quickly reduce the inflammatory reaction of lung tissue, but also can transform LTB4, which aggravates inflammatory reaction, into LTB5 series, which is less active, thereby significantly reducing pulmonary edema, improving the pulmonary vascular permeability [ 38 40 ]. Besides, as specific immunonutrients, omega-3 fatty can regulate the activity of lipid mediators, cytokines, and endothelial cell, thereby regulating the excessive inflammatory response of the body under infection and trauma [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pathophysiological changes were mainly due to increased Qs/Qt and imbalance of ventilation/blood flow ratio [ 37 ]. The application of omega-3 fatty acids not only can quickly reduce the inflammatory reaction of lung tissue, but also can transform LTB4, which aggravates inflammatory reaction, into LTB5 series, which is less active, thereby significantly reducing pulmonary edema, improving the pulmonary vascular permeability [ 38 40 ]. Besides, as specific immunonutrients, omega-3 fatty can regulate the activity of lipid mediators, cytokines, and endothelial cell, thereby regulating the excessive inflammatory response of the body under infection and trauma [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a Ghanaian longitudinal cohort, infants exposed to a less diverse nasopharyngeal microbiome had a higher small airway resistance compared to a more diverse microbiome at 4 years of age ( 67 ). Further, in a Mexican birth cohort study, prenatal omega 3 fatty acid supplementation in pregnancy did not influence preschool lung function at 36, 48 or 60 months ( 68 ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the application of omega-3 fatty acids rapidly reduced the inflammatory reaction of lung tissue, by transforming leukotriene B4, which aggravates inflammatory reaction, into leukotriene B5 series (less active), therefore reducing pulmonary edema and improving pulmonary vascular permeability 85 . Huang et al 86 concluded that omega-3 acids can improve respiratory function and respiratory status of acute lung injury (ALI) patients and suggested that omega-3 fatty acid could be a potential effective and safe strategy for ALI treatment.…”
Section: Discussionmentioning
confidence: 99%